Fungi diversity from different depths and times in chicken manure waste static aerobic composting. (September 2017) - Gu, Wenjie; Lu, Yusheng; Tan, Zhiyuan; Xu, Peizhi; Xie, Kaizhi; Li, Xia; Sun, Lili
Highlights: Fungi diversity research in the aerobic composting was studied with illumina sequencing. Time and depth are examined to reveal the fungi diversity variation in this study. Dirichlet multinomial mixtures mode was applied for illumina sequencing data analysis. Abstract: The Dirichlet multinomial mixtures mode was used to analyse illumina sequencing data to reveal both temporal and spatial variations of the fungi community present in the aerobic composting. Results showed that 670 operational taxonomic units (OTUs) were detected, and the dominant phylum was Ascomycota . There were four types of samples fungi communities during the composting process. Samples from the early composting stage were mainly grouped into type I and Saccharomycetales sp . was dominant. Fungi community in the medium composting stage were fallen into type II and III, Sordariales sp. and Acremonium alcalophilum, Saccharomycetales sp. and Scedosporium minutisporum were the dominant OTUs respectively. Samples from the late composting stage were mainly grouped into type IV and Scedosporium minutisporum was the dominant OTU; Scedosporium minutisporum was significantly affected by depth ( P  < 0.05). Results indicate that time and depth both are factors that influence fungi distribution and variation in c waste during static aerobic composting.